THOUGHT STOPPING ENHANCING SELF-ESTEEM OF PEOPLE WITH SCHIZOPHRENIA - Sulastri, Sulastri; Thahir, Andi; Rohayati, Rohayati (Universitas Airlangga, 2020)
Introduction: A person who has low self-esteem sees the environment in a negative way and considers it a threat. Schizophrenias patients with negative symptoms generally show a feeling of inferiority, this condition is a problem because of the cause of other problems, such as social isolation. The purpose of this research was to analyze the effect of giving thought stopping to self-esteem people with schizophrenia. Methods : This research uses quantitative approach the method used was the experimental design of pretest-posttest with control design. The population is the patient who was treated at the Custody. Sampling method in this research is by purposive sampling. Total sample is 90 respondents, divided into two groups, Intervention group 30 and control group 60 respondents. Measurement of data with client's self-esteem observation sheets before and after therapy. Results : The result of bivariate analysis was done using t-test obtained by p-value <0,005. There is a significant difference in patient self-esteem in the control group and intervention group after thought stopping. Conclusion: These results suggest there is influence of thought stopping with patient self esteem. Sex, length of illness and treatment history are not confounding factors. It is recommended to use thought stopping as one of the actions of nursing, especially on clients with self esteem problems.